2010
DOI: 10.1038/nrneurol.2010.159
|View full text |Cite
|
Sign up to set email alerts
|

Update on molecular findings, management and outcome in low-grade gliomas

Abstract: Low-grade infiltrating gliomas in adults include diffuse astrocytoma, oligoastrocytoma and oligodendroglioma. The current gold standard diagnosis of these tumors relies on histological classification; however, emerging molecular abnormalities discovered in these tumors are playing an increasingly prominent part in the process of tumor diagnosis and, consequently, patient management. The frequency and clinical importance of tumor protein p53 (TP53) abnormalities, deletions involving chromosomes 1p and 19q, O(6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 92 publications
3
85
1
Order By: Relevance
“…This is in agreement with Yan et al, 2009 [29] who found all studied oligoastrocytoma cases 10/10 (100%) stained diffusely with IDH1. These results were also in agreement to Bourne and Schiff 2010 [30] who reported that IDH1 expression in mixed oligoastrocytomas was ranged from 50% to 100%. As regard to epidermal growth factor receptor expression (EGFR); it was highly significant in distinguishing diffuse astrocytoma WHO grade II from reactive astrocytosis (Pvalue=0.00014).…”
Section: Resultssupporting
confidence: 93%
“…This is in agreement with Yan et al, 2009 [29] who found all studied oligoastrocytoma cases 10/10 (100%) stained diffusely with IDH1. These results were also in agreement to Bourne and Schiff 2010 [30] who reported that IDH1 expression in mixed oligoastrocytomas was ranged from 50% to 100%. As regard to epidermal growth factor receptor expression (EGFR); it was highly significant in distinguishing diffuse astrocytoma WHO grade II from reactive astrocytosis (Pvalue=0.00014).…”
Section: Resultssupporting
confidence: 93%
“…Finally, molecular markers, which are increasingly used for the assessment and management of LGG, were not included in the statistical analysis due to their recent introduction in clinical practice. 8 Ongoing and future randomized trials of LGG treatment will offer the opportunity to reveal the possible relationships between the molecular profiles and seizure outcome, detecting the histological subtypes more likely to result in drug-resistant epilepsy.…”
Section: Clinical Role Of Peritumoral Infiltrated Tissuementioning
confidence: 99%
“…4 Molecular markers involved in low-grade glioma pathways also play a critical role in determining prognosis. 5,6 The TP53 mutation is an early event in genetic pathogenesis that occurs in all types of cancer. The incidence of TP53 mutation in…”
mentioning
confidence: 99%